ANALISIS ASSESSMENT RATIO NILAI JUAL OBYEK PAJAK (NJOP) TANAH - Djasmanuddin . (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2010)
This research observed assessment ratio, a study about ratio between values for tax purpose with its market value, one of the use of assessment ratio was for assessment preservation at degree/level which was may accepted (uniformity), area/location determination for reappraisal (revaluation) and justice protection (equity) in determining the PBB. This research employed transversal data in the form of the Sales Value of Tax Object for the year 2008 – 2009 in Tegal, which specified by the office of service of land tax and building of Tegal city. This conclution taken from the research assessment ratio in Property Village Group and Property Housing Group and did not stay uniform. The average (mean) assessment ratio in the second group to leaning regresive character and stay under market value or underassessment.Keyword: Assessment ratio, Sales Value of Tax Object, PBB,